THE INFLUENCE OF PROBLEM-BASED LEARNING MODELS - COMPUTATIONAL THINKING (PBL – CT) ON THE ABILITY TO THINKING ANALYTICAL VIEW OF STUDENTS' INTEREST IN THE SUBJECT OF NATURAL SCIENCES - Hariana Gultom, Febrina; Saida Ulfa; Henry Praherdiono (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to find out whether there is an influence of the Problem Based Learning-Computational Thinking (PBL-CT) model on analytical thinking skills in terms of students' interest in Natural Sciences subjects. This research was conducted at the Kalam Kudus Christian Middle School in Malang in the 2022/2023 academic year. The design used in this study was a non-equivalent group design quasi-experiment. Retrieval of data using ten essay questions which are made according to indicators of analytical thinking ability and students' interest in science is measured by using a questionnaire. Data analysis was carried out by the Two Way Anova parametric test. Based on the results of the analysis carried out, the results were obtained: (1) there were differences in analytical thinking skills between students who were taught using the Problem Based Learning and Problem Based Learning - Computational Thinking (PBL-CT) learning models with a significance <0.05. (2) there is no difference in the ability to think analytically between students who have a high, medium, and low interest in learning science as shown by a significance value of 0.748 > 0.05. (3) there is an interaction between Problem Based Learning - Computational Thinking (PBL-CT) on students' analytical thinking skills in terms of students' interest in natural science subjects with a significance value of <0.05